TAX SOCIALIZATION MODERATES THE INFLUENCE OF KNOWLEDGE, QUALITY OF SERVICES AND TAX SANCTIONS ON INDIVIDUAL TAXPAYER COMPLIANCE - Desak Putu Devi Damayanti; I Ketut Jati (INTERNATIONAL JOURNAL OF ECONOMIC LITERATURE, 2024)
Taxpayer compliance is a form of taxpayer behavior that complies with its obligations to report taxes in accordance with applicable rules and regulations. Based on data from the Pratama Gianyar Tax Service Office (KPP), taxpayer compliance in 2019-2023 was at the highest, only reaching 80 percent in 2020. This supports the statement from the Ministry of Finance staff which stated that the realization of taxpayer compliance in Indonesia was less than 85 percent. percent. The lack of public awareness in reporting taxes is thought to be due to a lack of knowledge regarding mechanisms, tax reporting procedures and tax benefits. There are several factors that can influence taxpayer compliance, including tax knowledge, service quality and tax sanctions. This research aims to obtain empirical evidence regarding the influence of tax knowledge, tax service quality and tax sanctions on taxpayer compliance with tax socialization as a moderating variable at KPP Pratama Gianyar. This research uses an associative quantitative approach with data collection methods through distributing questionnaires. The population in this research is all WPOP at KPP Pratama Gianyar totaling 328,707 taxpayers. The sample for this research consisted of 100 respondents who were calculated using the Slovin formula with the accidental sampling method. The analysis technique used is moderating regression analysis. The research results show that knowledge of taxation and tax sanctions have a positive effect on taxpayer compliance, but service quality has no effect on taxpayer compliance. The results of the moderation regression analysis show that tax socialization does not strengthen the influence of tax knowledge and tax sanctions and tax socialization increases the influence of tax service quality on taxpayer compliance.